Meningkatkan Kemampuan Guru SD Negeri 4 Gedong Tataan dalam Mengembangkan Lembar Kerja Siswa (LKS) melalui In House Training Tahun 2022 - Sri Humairotun (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2023)
This research was carried out to improve the ability of teachers to develop Student Worksheets (LKS) which will be used for the implementation of learning for students. The research was carried out at SDN 4 Gedong Tataan with the aim of seeing an increase in the ability to make Student Worksheets (LKS) for teachers at SDN 4 Gedong Tataan. This study uses a reflective action research design carried out in 3 cycles. The research subjects were 12 teachers at SDN 4 Gedong Tataan. The results of data analysis for each cycle show that In House Training activities can improve the ability to make worksheets for SDN 4 Gedong Tataan teachers, Gedong Tataan District, Pesawaran Regency in 2022.